A Study on Influence of Industry Institute Interaction on Brand Building of Management Institutes in Pune - et. al., Yatish B. Ganganwar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Interaction Program of the Institute of Industry acts as a strong connection and bridge between educational institutions, especially BSchools and business centres in Pune. It is a well-established reality that trainees, known as Alumni, play a crucial role in establishing and improving the partnership and link between industry and the Institute. Over the last decade, the Indian higher education system has seen remarkable growth in developing into the world's third largest higher education system. In the framework of a dynamic global scenario, this sector has a tremendous potential to be a new driver of success. In an increasingly globalising environment, higher education institutions are called upon to resolve topics related to social, political, economic and growth. In order to study the significance, function and value of the Institute's growth, the researchers have agreed to undertake an exhaustive review of the perpetual and hormonal relationship of current Customer Interaction Practices with past B School students. There are more than 760 universities and 12,276 institutes of their own in India's higher education sector with these figures, one can imagine the level of competition in India's higher education sector.